Assessment of Anterior Loop of Inferior Alveolar Nerve and Its Anatomic Variations with Age, Gender, and Dentition Status in Indian Population: A CBCT Study. (31st August 2021) - Gupta, Anjali; Kumar, Sandeep; Singh, Siddharth Kumar; Kumar, Arunoday; Gupta, Abhishek; Mehta, Palkin
Abstract : Background . The posterior region of the mandible is more often related to iatrogenic errors, but the interforaminal region is also not spared for neurovascular complications. This study aimed to use CBCT images to evaluate the prevalence of anterior nerve looping and its variations with age, gender, and dentition status. Methods . This retrospective study was carried out by studying 600 CBCT scans retrieved from archival records of a CBCT center in Lucknow. The scans were inspected by two trained investigators. The length of the anterior loop was measured using the measuring tool of Carestream 3D imaging software. Descriptive and analytical tests were performed. Results . The prevalence of the anterior loop of the inferior alveolar nerve was found to be 56%. The prevalence was found to be more on the right side (29.0%) compared to the left side (27.0%). The most common anterior looping of the inferior alveolar nerve was type 3 followed by type 1. Males were found to have significantly higher loops compared to females. The number of loops was found to decrease significantly with age. The mean length of the loop was found to vary from 1.14 to 1.61 mm. Conclusion . The anterior looping of IAN is very much prevalent in the Lucknow population. The use of the CBCT technique and appropriate preplanning prior to surgery or implant placement should be performed to prevent nerve injury.